DETERMINAN PROFITABILITAS BANK UMUM KONVENSIONAL DI INDONESIA - Widya Puspa Andika (STIE Mandala Jember, 2018)
This research aims to analyze the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and operating expenses to operating income in partial on profitability that measured by Net Interest Margin (NIM). The population in this research is the Conventional Commercial Bank in Indonesia. The sampling method used is saturation sampling, taken from Conventional Commercial Bank that listed on otoritas Jasa Keuangan (OJK) This research was conducted during the period of 2012- 2015, was selected as many as 96 Conventional Commercial Bank that became a sample research. The data type used is quantitative data. This study used secondary data in the form of financial statements publication Conventional Commercial Bank in period 2012-2015 which is accessible via the official website of the OJK. The data analysis used in this research is multiple linear regression analysis. The results showed that partialy, CAR, LDR and BOPO significantly influenced the profitability that measured by NIM and they had negatif relationship with the NIM. Keywords: Profitability, NIM, CAR, LDR, BOPO.